2016
DOI: 10.1371/journal.pone.0166514
|View full text |Cite|
|
Sign up to set email alerts
|

Stillbirths at Term: Case Control Study of Risk Factors, Growth Status and Placental Histology

Abstract: ObjectiveTo investigate the proportion of stillbirths at term associated with abnormal growth using customized birth weight percentiles and to compare histological placental findings both in underweight stillborn fetuses and in live births.MethodsA retrospective case-control study of 150 singleton term stillbirths. The livebirth control groups included 586 cases of low-risk pregnancies and 153 late fetal growth restriction fetuses. Stillbirths and livebirths from low-risk pregnancies were classified using cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
6
13
1
Order By: Relevance
“…A number of studies showed that in women with CD recurrent pregnancy loss (RPL), fetal intrauterine deaths, fetal growth restriction (FGR), and small for gestational age (SGA) fetuses are more frequent. 13 A recent meta-analysis of 10 cohort studies shows that women with celiac disease (both treated and untreated) have a significantly higher risk of stillbirth (OR: 4.84). Beyond the nutrient deficiency characterized by lack of absorption of elements such as zinc, selenium, and folic acid, the role of anti-transglutaminase antibodies to impair trophoblast invasiveness and endometrial endothelial cells differentiation has been suggested as destructive element of early placentation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies showed that in women with CD recurrent pregnancy loss (RPL), fetal intrauterine deaths, fetal growth restriction (FGR), and small for gestational age (SGA) fetuses are more frequent. 13 A recent meta-analysis of 10 cohort studies shows that women with celiac disease (both treated and untreated) have a significantly higher risk of stillbirth (OR: 4.84). Beyond the nutrient deficiency characterized by lack of absorption of elements such as zinc, selenium, and folic acid, the role of anti-transglutaminase antibodies to impair trophoblast invasiveness and endometrial endothelial cells differentiation has been suggested as destructive element of early placentation.…”
mentioning
confidence: 99%
“…10,11 We have previously observed that fetuses which have not reached their genetically determined growth potential are at risk for adverse outcomes 12 and that some placental abnormalities (particularly obstructive lesions) may play a crucial role in underweight stillborn fetuses at term. 13 A recent meta-analysis of 10 cohort studies shows that women with celiac disease (both treated and untreated) have a significantly higher risk of stillbirth (OR: 4.84). 9 A 3.6 times higher prevalence of HLA-DQ2/DQ8 positivity was observed in women with RPL compared to women with at least two previous uncomplicated term pregnancies.…”
mentioning
confidence: 99%
“…To date, studies assessing risk factors associated with stillbirth have largely been population-based case-control studies (Flenady et al, 2011 provide a recent systematic review; recent studies include Mecacci et al, 2016 andKumbhare andMaitra, 2016), with a few studies only incorporating minimal geospatial information into the analysis (for example, DeFranco et al, 2015 andHall et al, 2014). For example, DeFranco et al, 2015 assessed whether exposure to increased levels of fine particulate air pollution (P M 2.5 ) was associated with stillbirth; geographic coordinates of maternal residence for each birth were linked to the nearest air monitoring station.…”
Section: Spatial Logistic Modelmentioning
confidence: 99%
“…To date, studies assessing risk factors associated with stillbirth have largely been population-based casecontrol studies (Flenady et al, 2011 provide a systematic review; recent studies include Kumbhare andMaitra, 2016 andMecacci et al, 2016), with a few studies incorporating minimal geospatial information into the analysis (for example, Hall et al, 2014 andDeFranco et al, 2015). To our knowledge, no analysis of point patterns associated with stillbirth exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation